Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Alfian Telaumbanua; Dermawan Zebua (CV. SINAR HOWUHOWU, 2026)
Employee performance is one of the determining factors for an organization's success in achieving its stated goals. Employee performance is influenced by various factors, including motivation and work discipline. This study aims to analyze the influence of motivation and work discipline on employee performance, both partially and simultaneously. The research method used is a quantitative method with a descriptive and verification approach. Data collection techniques were carried out by distributing questionnaires to employees as research respondents. The data obtained were analyzed using multiple linear regression analysis. The results of the study indicate that work motivation has a positive and significant effect on employee performance. Work discipline has also been shown to have a positive and significant effect on employee performance. Simultaneously, motivation and work discipline have a significant effect on employee performance. These findings indicate that improving employee performance can be achieved through efforts to increase motivation and implement consistent work discipline in the organizational environment